Alpha-Bisabolol: a review of bioactive properties antiphlogistic (Research, Society and Development, 2021)
The present work aimed to identify and systematize scientific works that attribute to alpha-bisabolol (BISA) antiphlogistic activities. This is a literature review, whose selection of articles was carried out in the PubMed, Web of Science, and Science Direct databases. For data collection purposes, the PRISMA guidelines and the Bardin method were used. The search strategy identified 257 articles that after screening were eligible for the review 37. The inclusion criteria defined were: original articles, review articles, experimental research, clinical trials, in vitro, in vivo and silico, meta-analysis studies, in English, Spanish and Portuguese language. Only works with full texts, accessible and in the study timeline (January 2008 to July 2021) were used. Duplicate literature, paid and unrelated to the research objective, was excluded. Regarding the approach with specific themes, we have that: 22 (59.45 %) articles refer to the anti-inflammatory, antioxidant, and analgesic effects of BISA, 1 (2.70 %) review publication and 14 (37.83 %) investigate the actions of sesquiterpene on the integumentary tissue. Of all selected studies, 89.18 % (n=33) were carried out in a laboratory environment and only 10.82 % (n=4) used another methodological source. There is currently little evidence to report safe studies on integumentary preparations using BISA. However, available studies on the antiphlogistic actions of BISA prove its anti-inflammatory, analgesic, and antioxidant efficacy. Therefore, the authors consider that the sesquiterpene has clinical potential to be used in inflammatory processes of different etiologies, but further investigations are needed.